Implementation of Maqashid Syariah in the Management of Regional Assets: Hifz al-Mal and Good Governance Perspective - Sriyani; Arifah Fibri Andriani; Ria Dewi Ambarwati (IKONOMIKA, 2026)
The implementation of Maqashid Syariah in the management of Regional Assets (BMD), especially the maintenance of Hifz al-Mal assets, and the application of good governance principles. Asset management problems such as limited human resources, inaccurate recording, and weak inventory are often found in the regions even though regional financial performance has received a fair opinion without being conveyed. This study aims to explore the problems that occur in BMD management using a qualitative method with an analytical descriptive approach. Primary data were obtained through interviews and Focus Group Discussions (FGDs), while secondary data were obtained through literature studies and reports. Respondents were selected by purposive sampling and analysis was carried out using the Quantitative Strategic Planning Matrix (QSPM). The results of the study found 17 strategic factors that influence BMD management. The most feasible strategic priority is to conduct a periodic BMD inventory within the framework of Hifz al-Mal to realize Maslahat kulliyat related to the public interest that includes the welfare of the entire community.